Influence of Short-Course Antenatal Antiretroviral Therapy on Viral Load and Mother-To-Child Transmission in Subsequent Pregnancies among HIV-Infected Women. Issue 2 (February 2013) - French, Clare E; Tookey, Pat A; Cortina-Borja, Mario; De Ruiter, Annemiek; Townsend, Claire L; Thorne, Claire
Background: HIV-infected women not requiring treatment for their own health usually receive short-course anti-retroviral therapy (ART) during pregnancy. Little is known about the effect of this on response to HAART in subsequent pregnancies. Methods: We analysed data from the UK and Ireland's National Study of HIV in Pregnancy and Childhood for 2000–2010. Analyses were restricted to live births among women not on ART at conception but receiving antenatal HAART. We compared risk of detectable viral load at delivery and mother-to-child transmission in two pregnancy groups: 'ART-naive' and 'HAART-experienced' (≥7 days of HAART during previous pregnancy). Multivariable analyses were conducted using logistic regression. Results: There were 5, 372 pregnancies in the ART-naive group and 605 in the HAART-experienced group. Overall, there was weak evidence of an increased risk of detectable viral load in the HAART-experienced group (adjusted odds ratio [aOR] 1.27; 95% CI 1.01, 1.60); however, the increased risk was apparent only among women who previously received non-nucleoside reverse transcriptase inhibitor-based HAART (aOR 1.81; 95% CI 1.25, 2.63), and not among those with previous protease-inhibitor-based HAART exposure (aOR 1.08; 95% CI 0.81, 1.45). There was no difference in mother-to-child transmission risk between the ART-naive and HAART-experienced groups (aOR 0.42; 95% CI 0.10, 1.78), although the number of transmissions was small. Conclusions: We found no increased risk of detectable viral load at delivery among women exposed to short-course, protease-inhibitor-based HAART during a previous pregnancy. However, women with prior exposure to non-nucleoside reverse transcriptase inhibitor-based HAART appeared to be at increased risk of not adequately suppressing the virus. These findings highlight the need for careful management of HIV-infected women presenting with repeat pregnancies.